Alloprocoptic selection: A mode of natural selection promoting polymorphism - Serradilla, Juan M. (1983)
The fitness effect of genetic variation at three loci coding for enzymes is studied in Drosophila melanogaster. The fertility of a female is determined by the female genotype as well as by the genotype of the male with which she mates. Significant interactions exist between female and male genotype, so that the fertility of a given mating combination cannot be predicted from the average fertility of the two genotypes involved. Multiple stable equilibria are possible when such interactions exist. At two loci, the fertility is greater than expected when the two mating individuals are homozygous for different alleles and smaller than expected when they are homozygous for the same allele. This mode of selection in which association of opposites increases their fitness is herein named alloprocoptic selection. It will contribute to maintaining genetic polymorphism in nature.